Pengaruh Pendidikan Kesehatan terhadap Pengetahuan Ibu Hamil tentang 1000 Hari Pertama Kehidupan - Endah Mulyaningsih; Sukarni Setya Ningsih (Universitas Malahayati Lampung, 2024)
ABSTRACT The First 1000 Days of Life period is a period that determines the quality of life in the future, where the consequences for babies at this time are permanent and cannot be corrected, therefore this period is often referred to as the